Feelings of professionals working in Primary Care during the COVID-19 pandemic (Research, Society and Development, 2022)
Goal: Comprehend the feelings of professionals who work in Primary Care (AB) during the COVID-19 pandemic. Method: It's a qualitative study, developed with the health care team of a Basic Health Unit (UBS), which is located in a medium-sized county in the state of Santa Catarina, in November 2020. During the data collection, three focus groups were held with the participation of professionals from different categories.  The focus groups were conducted using a guiding script and the discussions were audio-recorded and then later transcribed. The material was treated by thematic content analysis. The research protocol strictly followed every ethical requirements and was approved by the Research Ethics Committee of the Fronteira Sul Federal University (UFFS), through opinion 4,301,348 of September 20, 2020 (CAAE: 37110520.7.0000.5564). Results: When analyzing the feelings of health care professionals who worked in Primary Care during the COVID-19 pandemic, it was found that these feelings impacted the personal lives of professionals, their service to the community and the conviviality with their families. From the speech clippings of the transcribed material, five empirical categories emerged, understood as feelings of the analyzed professionals: psychic suffering, pressure, fear, anguish and frustration. Conclusion: The COVID-19 pandemic negatively influenced the mental health of health professionals, since one can perceive the presence of psychological illness resulting from work.